Lalela uLwandle (Listen to the Sea): Interdisciplinary approaches and embodied engagements in thinking with ocean/s - Wiese, Abigail (Critical Studies in Teaching and Learning, 2023)
This article is a self-reflexive engagement on the performance, Lalela uLwandle (Listen to the Sea, 2019) created by the South African collective, Empatheatre. I engage with the performance in an affective and embodied way, commenting on my experience of watching myself, watching Lalela uLwandle. I ask how the performance contributes to knowledge production on the ocean, and how it might facilitate agentive engagements with its current health tragedy. To do so I examine the modalities employed in Lalela uLwandle: research-creation, empatheatre as methodology, indigenous storytelling and material aesthetics. I propose that, through its specific methodological framings and performance aesthetics, Lalela uLwandle repositions the (disconnected) audience member to reconnect with the human and the non-human. I suggest that the performance aesthetics enacted in the methodological approaches used by Empatheatre offer audiences an opportunity to acknowledge their own precarious construction in relation to the ocean by considering their historical entanglements with it.